Treating patients with advanced heart failure in a community-based multidisciplinary team clinic is associated with significant reduction of healthcare utilization and costs. (14th October 2021) - Weinstein, J.M; Simon-Tuval, T; Kiselnik, D; Hemo, Z; Amitai, V; Stanovski, Y; Sidi, A; Kidman, G; Sharf, A; Greenberg, D
Abstract: Background/Introduction: Heart failure (HF) care imposes a major economic burden, accounting for 1–3% of healthcare expenditure in developed countries. The greatest proportion of this cost (60%-70%) is accounted for by hospitalizations. A multidisciplinary team (MDT) approach in HF management is a key recommendation in international guidelines, to reduce mortality and HF hospitalization. Purpose: To investigate whether a community-based MDT in an HF unit (HFU) had an impact on patients' healthcare utilization (HCU), and their associated costs. Methods: A retrospective cohort study was conducted among members of the country's largest HMO, who visited at least once in a regional community-based HFU, established to provide ambulatory specialist care for patients with advanced HF, emphasizing patients in NYHA functional class III and IV, especially those with recurrent hospitalizations. HCU data were obtained from the HMO's claims data for 12 months before and after first HFU visit. Results: Our cohort consisted of 962 patients, of whom 843 (87.6%) completed at least 12 months of follow-up, and 119 (12.4%) died during the 12 months following their first HFU visit. Both groups were comparable with regard to sex, socioeconomic status, Charlson comorbidity index, prevalence of IHD and/or carotid artery disease, AF, obesity, and chronic pulmonary disease. Those who died within 12 months were older, had more hypertension, hyperlipidaemia, diabetes, chronic renal disease and malignancy but were less likely to be smokers or to have supplementary health insurance coverage. There was a significant reduction in the total average HCU costs of the entire study population 12 months after the first HFU visit (12, 675 after vs. 13, 188 before, p=0.014). However, while a reduction in these costs was observed among patients who completed 12 months of follow-up (11, 955 after vs. 13, 112 before, p<0.001), an increase in these costs was observed among patients who died during follow-up (17, 774 after vs. 13, 728 before, p=0.015). These opposite trends stem from a decrease (3, 540 after vs. 4, 941 before, p<0.001) versus increase (10, 932 after vs. 6, 733 before, p=0.002) in hospitalization costs of these groups, respectively, and an increase (1, 272 after vs. 928 before, p<0.001) versus decrease (799 after vs. 1, 116 before, p<0.001) in medication costs of these subgroups, respectively. Conclusion(s): Intensification of therapy by a dedicated MDT significantly reduced costs of HCU, predominantly because of a decrease in hospitalizations. This saving was noted even when including patients who died within a year of commencing treatment in our HFU (a group in whom healthcare costs are known to be excessive). A widespread establishment of dedicated community-based units, should be encouraged. Funding Acknowledgement: Type of funding sources: None.